Human talent management strategy to improve job performance in a bank - Checa-Llontop, Luis A. (2020)
In this research, a diagnosis of the current state of work performance of the Company CMAC Piura S.A.C. was made. The objective is to elaborate a Strategy of Human Talent Management that helps to implement, develop and evolve skills, aptitudes and knowledge that allow to give improvement to the research problem. The research is of descriptive - propositional design because it seeks to describe characteristics of human talent management and how to apply it correctly will help with the research problem presented. A survey was applied to the sample corresponding to 36 people and using the SPSS program we obtained validity of Cronbach's alpha 0.862 and found as results of the statistical tables the lack of opportunities for growth and training, lack of knowledge of strategic plans, no good communication between areas, among other results. Based on this, a strategy is built that consists of 4 stages that seek to manage talent from the moment it is hired and to provide feedback and follow-up, thus solving the problem in the work performance. It is concluded that the elaboration of a Human Talent Management Strategy will help to improve the performance of CMAC Piura S.A.C. collaborators.